Safety Aspects and Rational Use of Testosterone Undecanoate in the Treatment of Testosterone Deficiency: Clinical Insights - Campbell K; Muthigi A; Ghomeshi A; Schuppe K; Sandler MD; Ramasamy R (Drug, Healthcare and Patient Safety, 2023)
Katherine Campbell,1 Akhil Muthigi,1 Armin Ghomeshi,2 Kyle Schuppe,3 Max D Sandler,4 Ranjith Ramasamy1 1Desai Sethi Urology Institute, University of Miami, Miami, Fl, 33136, USA; 2Herbert Wertheim College of Medicine, Florida International University, Miami, FL, 33199, USA; 3Washington State University Elson S. Floyd College of Medicine, Spokane, WA, 99202-2131, USA; 4University of Miami Miller of Medicine, Miami, Fl, USACorrespondence: Ranjith Ramasamy, Desai Sethi Urology Institute, University of Miami, 1120 NW 14th St, Miami, Fl, 33136, USA, Tel +1 305-243-6090, Email ranjithrama@gmail.comAbstract: Testosterone deficiency is diagnosed by a serum total testosterone level below 300 ng/dL in combination with symptoms such as decreased energy and libido. These symptoms can be ameliorated by restoring serum testosterone to the physiologic range with testosterone therapy (TT). There are numerous forms of testosterone therapy, such as injectable, transdermal, nasal, and subcutaneous applications. There are also multiple formulations of injection, such as testosterone cypionate, testosterone enanthate, and testosterone undecanoate. Testosterone undecanoate (TU) is a long-acting ester formulation of testosterone that can be provided in an injectable or oral form. Oral testosterone undecanoate is marketed as Andriol, Jatenzo, Tlando, and Kyzatrex. Oral TU provides a convenient option for many patients, which may increase compliance with TT. Injectable testosterone undecanoate is marketed as Aveed and Nebido. Injectable TT remains the most cost-effective therapeutic option and is appropriate for most patients as an initial therapy. This review describes the pharmacokinetics of these testosterone undecanoate products and provides a guide for prescribers using these medications. While many forms of testosterone are appropriate for TT, a patient-centered discussion focused on goals of care should best guide physician prescription of these medications.Keywords: testosterone, testosterone deficiency, testosterone therapy, hypogonadism in male